PD-1 inhibitor versus bevacizumab in combination with platinum-based chemotherapy for first-line treatment of advanced lung adenocarcinoma: A retrospective-real world study - Huang, Zhe; Zhou, Chunhua; Xiong, Yi; Yang, Feng; Zeng, Fanxu; Jiang, Wenjuan; Zhang, Yongchang; Yang, Haiyan; Liu, Li; Zeng, Liang; Yang, Nong; Wang, Zhan (Frontiers in Oncology, 2022)
background： Chemotherapy combined with immunotherapy or anti vascular therapy are both recommended by guidelines for first-line treatment of lung adenocarcinoma, However, no head-to-head clinical trial has ever compared which strategy is the optimal choice. This real-world retrospective study was designed to compare the efficacy and treatment-related adverse events of immunotherapy and bevacizumab in combination with chemotherapy. Patients and Methods: From January 2018 to March 2021, 276 patients with advanced lung adenocarcinoma received chemotherapy combined with either bevacizumab or PD-1 inhibitors. 139 patients were treated with chemotherapy combined with bevacizumab, while 137 patients were treated with chemotherapy combined with PD-1 inhibitors. After receiving 4 cycles of combination therapy, all patients received maintenance therapy till disease progression. The primary endpoint was progression‐free survival (PFS) and overall response rate (ORR), and secondary endpoints were overall survival (OS), disease control rate (DCR), and adverse events (AE). Results: Comparing to anti-vascular therapy, Patients who received immunotherapy achieved better PFS (7.3 months VS. 10 months, p= 0.002) while ORR (40.9% VS 51.1%, p =0.093) as well as OS (18 months VS. 24 months p= 0.060) had no statistical difference between the two group. In the PD-L1-negative population, there was no statistical difference in PFS and OS between the two groups. (8.0 months VS. 6.0 months, p = 0.738; and 19 months VS. 13 months, p = 0.274) In the PD-L1-positive population, there was a significant benefit in PFS in the population receiving immunotherapy. (7.0 months VS. 10.0 months, p = 0.009) Proteinuria and hypertension occurred more frequently in the bevacizumab-treated group, (p = 0.001 and p = 0.002) whereas immune-related pneumonia and hypothyroidism occurred more frequently in the immunotherapy-treated group. (p = 0.007 and p = 0.030) Conclusions: The addition of PD-1 inhibitor significantly superior to bevacizumab in terms of PFS among patients with advanced lung adenocarcinoma. PD-L1 positive patients appeared to exhibit better PFS, OS and ORR. Toxic reactions were manageable in both groups.